RETRIBUTION COLLECTION PRACTICES OF STREET VENDORS FROM THE PERSPECTIVE OF SHARIA ECONOMIC LAW IN SIGLI CITY OF INDONESIA - Ari Ananda; Boihaqi bin Adnan (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
Informal economic activities such as street vending have become an integral part of the socio-economic dynamics in urban areas, including Sigli City. The presence of street vendors not only meets the daily needs of the community but also serves as a livelihood for the lower-middle economic class. However, the practice of managing and collecting retribution fees from street vendors still presents various issues, particularly concerning legality and fairness. This study aims to analyse the retribution collection practices imposed on street vendors in Sigli City from the perspective of Islamic economic law. Using a descriptive qualitative method, data were obtained through field observations, interviews with vendors and local authorities, and a review of regulatory documents. The findings reveal that retribution is often collected by unauthorized parties, such as parking attendants, without formal contracts and without being based on official regulations issued by the local government. These practices are considered contrary to Islamic economic principles, which emphasise contractual clarity, justice, and public welfare (maslahah). Elements of uncertainty (gharar), injustice (zulm), and unauthorised authority were identified in the field. Therefore, a reformulation of retribution policy based on maqashid shariah is necessary to establish a system of governance that is fair, transparent, and sustainable for all stakeholders involved.